Geotechnical evaluation of gully erosion and landslides materials and their impact in Iguosa and its environs, southern Nigeria - Godwin Okumagbe Aigbadon; Azuka Ocheli; Ernest Orji Akudo (Environmental Systems Research, 2021)
Abstract Background Detailed field surveys and geotechnical evaluation of soils in Iguosa and its environs, Southern Nigeria, were undertaken to determine the root causes, mechanisms, and impacts of landslides and gully erosion. This was done to suggest appropriate mitigation measures to reclaim the affected land and prevent future occurrences in the study area. Results Field study revealed high elevations, a steep slope, high rainfall and inadequate drainage systems. Also, human activities and socio-cultural activities have contributed to the large lateral extents in depths and widths of the landslides and gullies in the study area. The geotechnical analyses reveal that soil samples from SB1, SB2, SB6 and SB7 lithological units are mainly sandy clay with a coefficient of permeability ranging from 3.5 × 10−4 to 4.2 × 10−4 cm/s, the cohesion ranges from 27 to 28 kƿa and angle of internal resistance ranges from 27° to 30° respectively. The plastic limit ranges from 2 to 4, and liquid limit ranges from 33 to 38, and the plasticity index ranges from 30 to 36. Ajali sand units SB3, SB4, SB8 and SB9, consist of coarse-grained sand with no plasticity. The coefficient of permeability ranges from 2.8 × 10−4 to 3.2 × 10−4 cm/s, the cohesion range from 10 to 18 kƿa, angle of internal resistance 24° to 26°, respectively. The soil samples from SB5 and SB10 lithological units are silty-clay with a coefficient of permeability of 4.6 × 10−4 to 4.8 × 10−4 cm/s. The cohesion of 45 to 46 kƿa, and angle of internal resistance of 37﻿° to 40°, respectively. The plastic limits ranges from 35 to 36, and liquid limit is 76, and the plasticity index ranges from 40 to 41. Conclusion Field survey and geotechnical evaluations of the soils revealed that high elevation, a steep slope and the geotechnical properties of the soils were the initial conditions that initiated landslides and gully developments in the study area. This has also been influenced by rainfall, poor vegetation, inadequate drainage systems, and human activities as well as socio-cultural activities. Over four hundred and thirty-two houses and farmlands and other properties have been damaged and abandoned in the study area. Covering the landslide areas with impermeable layers/materials, diverting surface water away from the landslide areas, enacting laws to prevent the erection of structures on landslide prone-areas, sound drainage systems, the use of biotechnical slope and bioengineering methods, afforestation and re-vegetation were the proposed mitigation measures to tackle this menace in the study area.